1984
DOI: 10.1007/bf01726905
|View full text |Cite
|
Sign up to set email alerts
|

Steroid receptor status of focal-nodular hyperplasia of the human liver

Abstract: As with normal human liver, both focal nodular hyperplasia (FNH) of the liver and a hepatocellular carcinoma were found to contain low levels of high affinity estrogen-binding components. In low-salt sucrose gradients the estrogen binders sedimented at 4S and 8S. Specificity studies indicated a requirement for estrogenic hormones. Progestin-binding studies using labeled and unlabeled ORG 2058 revealed high levels of specific binding in FNH and normal liver cytosol, whereas only insignificant amounts of ORG 205… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Therefore, prolonged OC intake and pregnancy have been suggested to be related to FNH pathogenesis (Davis et al 1975;Bartok et al 1980;Tajada et al 2001). Low levels of estrogen receptors have been detected in FNH (Bojar et al 1984), whereas expression of progesterone receptors was not demonstrated in FNH (Kubota et al 2001). However, in a large study on 216 women, neither the size nor number of FNH lesions were influenced by OC use, and pregnancy was not associated with FNH changes or complications (Mathieu et al 2000).…”
Section: Fnh and Fnh-like Nodules Associated With Steroid Hormonesmentioning
confidence: 99%
“…Therefore, prolonged OC intake and pregnancy have been suggested to be related to FNH pathogenesis (Davis et al 1975;Bartok et al 1980;Tajada et al 2001). Low levels of estrogen receptors have been detected in FNH (Bojar et al 1984), whereas expression of progesterone receptors was not demonstrated in FNH (Kubota et al 2001). However, in a large study on 216 women, neither the size nor number of FNH lesions were influenced by OC use, and pregnancy was not associated with FNH changes or complications (Mathieu et al 2000).…”
Section: Fnh and Fnh-like Nodules Associated With Steroid Hormonesmentioning
confidence: 99%